Effect of creep on refractory masonry wall subjected to cyclic temperature loading - Gajjar, Pratik Naresh (2019)
Refractory masonry in its application is usually exposed to chemical, thermal and mechanical loads in service. Mechanical loads develop from the thermal expansion of the refractories which is confined either by the regions of different temperature within the structure or by the boundary conditions. The aim of this work is to investigate, using numerical simulation, the influence of creep on the thermomechanical behavior of the refractory masonry. Different modeling approaches are used in order to produce thorough parametric and sensitivity studies. The investigation is specially focused on the adverse effect of creep on the stability of the masonry wall. The comparison is carried for different loading cycles by taking consideration of creep effect and without creep effect. The results presented in this paper provide, for specific boundary conditions and thermal loading, the evolution of out-of-plane displacement of the masonry wall while considering the effect of material specific primary creep at different high temperatures. For this specific case, it was found that the reduction in out-of-plane displacement due to creep is considerable and cannot be overlooked.